The Eminent Pioneer Translator of Chinese Classical Poetry, Yong Ingkawate: Works and Identities - Jiraphas, Charassri (Journal of the Faculty of Arts, Silpakorn University, 2021)
This article aims to discuss Yong Ingkawate’s Thai translation of Chinese Classical Poetry and its dissemination. The analysis of identities in the works studied is also presented. From the study, it was found that Yong had translated a large number of Chinese classical poetry which covered almost all periods of Chinese literature. His works show that he was a pioneer and eminent in Thai translation of Chinese classical poetry. His translations conveyed both senses and sensibilities. His informal academic style, adding historical and cultural supplementary details to the translated works, has led to his translations being published and republished on many occasions. As a result, Yong Ingkawate, has been a significant role model and inspiration for younger translators. Furthermore, his translated works are important academic documents for the study on Thai-Chinese history.